Methods of Forming Cultural Immunity in Adolescent Students Based on the Gender Approach - Tojibayeva Khilolakhan Makhmutovna (International Journal on Integrated Education, 2022)
The article discusses the methodological possibilities of games, incentives, and dilemma methods in the formation of cultural immunity in adolescent students based on the gender approach. In addition, it was emphasized that the mobilization of them to perform public tasks is of particular importance in the formation of the ability to follow cultural behavior norms in teenagers, and collective tasks are the most effective means of socializing teenagers. Teaching adolescent students to self-control, behave in public places, and follow the norms of interpersonal relations also serves to form cultural immunity in them.